2006
DOI: 10.1111/j.0022-1112.2006.001012.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in abundance, return rate and life histories of previously spawned Atlantic salmon in a large subarctic river

Abstract: The 30 year time series analyses revealed large temporal variation in the return rates and a recent increase in abundance of previous spawning Atlantic salmon Salmo salar in the River Teno, northern Scandinavia. The mean proportion of repeat spawners was 7 and 4% in the total Atlantic salmon catch and 9 and 22% in multi‐sea‐winter (MSW) catch component for females and males, respectively. Previous spawners constituted on the average 7% of the catch in mass but up to 20%(31 t) and 30%(19 t) in 2003 and in 2004,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 33 publications
4
84
0
Order By: Relevance
“…Conserving kelts in the river before outmigration might be of importance even in rivers with low proportions of repeat spawning, as the contribution of repeat spawners might be significant not only due to their numbers but also due to their mass as Niemelä et al (2006) suggested in their time-series from River Tana. In addition, the majority of the returning repeat spawners are females (Niemelä et al 2006, own unpublished data), which further increase their significance, as the females are usually the limiting factor to production.…”
Section: The Potential Significance Of Kelt Survival For Repeat Spawningmentioning
confidence: 99%
See 2 more Smart Citations
“…Conserving kelts in the river before outmigration might be of importance even in rivers with low proportions of repeat spawning, as the contribution of repeat spawners might be significant not only due to their numbers but also due to their mass as Niemelä et al (2006) suggested in their time-series from River Tana. In addition, the majority of the returning repeat spawners are females (Niemelä et al 2006, own unpublished data), which further increase their significance, as the females are usually the limiting factor to production.…”
Section: The Potential Significance Of Kelt Survival For Repeat Spawningmentioning
confidence: 99%
“…Kelts can potentially return as repeat spawners, and even though typically less than 11% return to breed again (Belding, 1934;Fleming, 1998), in some populations the return rate is high, and in some instances increasing (Dempson et al, 2004;Jonsson and Jonsson, 2004;Niemelä et al, 2006). Furthermore, the kelts that do return as repeat spawners might contribute more to the overall population fitness than their sheer numbers would indicate due to their increased size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations located in southern European rivers are expected to be particularly affected by global warming (Valiente et al 2010). Poor salmon production associated with changes in life histories (for example, return rates) were all related to unfavorable climatic conditions, such as increasing seawater and freshwater temperatures (Jonsson and Jonsson 2004;Niemela et al 2006). Homing was shown to be less strict in southern regions because of opportunistic returns driven by unfavorable environmental conditions (Moran et al 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Both strategies maintain genetic diversity and reduce demographic risks by increasing the number of unique adult pairings across years (Crespi and Teo 2002;Niemelä et al 2006). Iteroparous individuals may also be more productive than semelparous conspecifics because of higher cumulative fecundity and lifetime fitness (Fleming and Reynolds 2004).…”
Section: Introductionmentioning
confidence: 99%